Local Culture-Based Multimodal E-Book in ESP Classroom: Learners’ Voices at Hindu Higher Education - Ni Nyoman Tantri (Indonesian Postgraduate Foreign Language Education Association, 2025)
Previous studies have acknowledged that non-English Majors learners (ESP learners) remained in low category of English proficiency level. Hence, some scholars agreed that developing teaching materials that closely related to the learners’ real life could be one of alternative solution to cater this problem. This present study aimed at exploring the needs, wants, and difficulties in learning English, particularly to ESP classroom. This preliminary stage was done in order to develop a multimodal e-book which is oriented to the local culture as for the representation of the learners’ real life. The qualitative design with a content analysis was employed in this study. The data were accumulated through interview and questionnaire. There were 5 ESP learners acted as the participants interviewed, and 25 sophomore students of IAHN TP Palangka Raya were the respondents answered the questionnaire. The data of this study were analyzed descriptively. The result showed that the learners perceived that the multimodal e-book-oriented topics on local culture could help them easier learning English and would lead them to improve their English proficiency level. Then, based on the learners’ needs, wants, and difficulties, it showed that the learners required a multimodal book that could represent their discipline or specific field which presented through various modes of learning media which is supported by various learning methods.